2003
DOI: 10.1126/science.1087919
|View full text |Cite
|
Sign up to set email alerts
|

Encoding Predictive Reward Value in Human Amygdala and Orbitofrontal Cortex

Abstract: Adaptive behavior is optimized in organisms that maintain flexible representations of the value of sensory-predictive cues. To identify central representations of predictive reward value in humans, we used reinforcer devaluation while measuring neural activity with functional magnetic resonance imaging. We presented two arbitrary visual stimuli, both before and after olfactory devaluation, in a paradigm of appetitive conditioning. In amygdala and orbitofrontal cortex, responses evoked by a predictive target st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

88
762
13
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,050 publications
(869 citation statements)
references
References 27 publications
88
762
13
6
Order By: Relevance
“…Similar results in the amygdala, which together with the OFC constitutes part of the structural appetitive/approach network that underpins Pavlovian incentive and motivated behavior (Gottfried et al, 2003;O'Doherty et al, 2003), and is commonly associated with regulation of emotion (Hare et al, 2005), lend further support for greater task-related emotional suppression or similar competing, extraneous or idiosyncratic factors operating in the "flat" cocaine subgroup. However, because the current correlation between SSG-R and OFC/IFG was driven by the "non-flat" cocaine group (and not the "flat" cocaine group), this interpretation remains tentative.…”
Section: The Ofc/ifg In the Constrained Subjective Sensitivity To Relmentioning
confidence: 58%
“…Similar results in the amygdala, which together with the OFC constitutes part of the structural appetitive/approach network that underpins Pavlovian incentive and motivated behavior (Gottfried et al, 2003;O'Doherty et al, 2003), and is commonly associated with regulation of emotion (Hare et al, 2005), lend further support for greater task-related emotional suppression or similar competing, extraneous or idiosyncratic factors operating in the "flat" cocaine subgroup. However, because the current correlation between SSG-R and OFC/IFG was driven by the "non-flat" cocaine group (and not the "flat" cocaine group), this interpretation remains tentative.…”
Section: The Ofc/ifg In the Constrained Subjective Sensitivity To Relmentioning
confidence: 58%
“…In line with this suggestion, human appetitive conditioning has generally been successfully evidenced using subjective measures (e.g., US expectancy and CS valence ratings; Van Gucht, Baeyens, Vansteenwegen, Hermans, & Beckers, 2010; Van Gucht, Vansteenwegen, Van den Bergh, & Beckers, 2008), behavioral measures (e.g., reaction times; Pool, Brosch, Delplanque, & Sander, 2014; Pool, Delplanque et al, 2014; Van Gucht et al, 2008), or brain activity (e.g., Delgado, 2007; Franken, Huijding, Nijs, & van Strien, 2011; Gottfried, O'Doherty, & Dolan, 2002, 2003; Klucken et al, 2009; Prévost, McNamee, Jessup, Bossaerts, & O'Doherty, 2013), whereas the use of peripheral physiology measures (e.g., skin conductance response, SCR) has mainly yielded mixed or inconclusive results (see, e.g., Hermann et al, 2000). Developing psychophysiological indicators of appetitive conditioning thus constitutes an important purpose to eventually remedy the scarcity of knowledge about key mechanisms involved in emotional learning in humans.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fMRI studies of odor–visual association (or integration) have shown that a visual cue previously associated with an odor can, in the absence of odor stimulation, elicit neural activity in the primary olfactory cortex (Gottfried et al. 2003, 2004). In this paradigm, stimulus‐evoked activity within the hippocampus and orbitofrontal cortex was also shown to be experience dependent (Gottfried et al.…”
Section: Introductionmentioning
confidence: 99%
“…In this paradigm, stimulus‐evoked activity within the hippocampus and orbitofrontal cortex was also shown to be experience dependent (Gottfried et al. 2003). Importantly, olfactory associative memory can occur very quickly, in some cases with a single trial (Sullivan et al.…”
Section: Introductionmentioning
confidence: 99%